Total Distal Radioulnar Joint Arthroplasty for Paget's Disease of Bone - Mullett, Patrick H.; Willems, Joost; Christensen, Thomas J. (Journal of Wrist Surgery, 2020)
Background Distal radioulnar joint (DRUJ) and ulnocarpal pathology, such as ulnocarpal impaction, are relatively common causes of ulnar-sided wrist pain. We herein report a rare case of ulnocarpal impaction and DRUJ arthropathy due to Paget's disease of bone (PDB) in the ulna.Case Description A 65-year-old, right-hand-dominant male was diagnosed with right-sided ulnocarpal impaction secondary to PDB. While diagnosing the cause of this patient's ulnar wrist pain was relatively straightforward, the management of his pain and symptoms was less so. After a thorough discussion with the patient regarding medical versus surgical management, and after presenting all available surgical options, he opted for a total distal radioulnar joint arthroplasty (TDRUJA). At 3-year follow-up, his wrist is pain-free, has excellent functionality, near-normal motion, and he is highly satisfied.Literature Review Currently, there are no specific recommendations for surgical management of PDB in the ulna, causing ulnocarpal impaction. While resection of the pathologically enlarged ulnar head (Darrach procedure) and the Suavé-Kapandji (SK) procedure are standard surgical treatment options, a major known disadvantage of these procedures is painful ulnar impingement syndrome. TDRUJA, a relatively new treatment option, provides good long-term outcomes with high patient satisfaction and protects from ulnar impingement.Clinical Relevance Since recommendations are lacking for surgical management of PDB, we propose that the TDRUJA be considered as an effective surgical option for the management of PDB causing ulnocarpal impaction. Furthermore, this can reduce the incidence of ulnar impingement, especially for patients who have pathologically enlarged ulnas that are prone to impingement.
Keywords: Scheker prosthesis; semiconstrained linked total distal radioulnar joint arthroplasty; ulnar impingement syndrome; Paget's disease of bone; ulnocarpal impaction